Integrated optical and wireless access networks: from the energy consumption perspective - Ramli, Arnidza (Asian Research Publishing Network (ARPN), 2015)
Integrated optical and wireless technologies is one of the emerging access network solution that offers to combine the robustness and high capacity of optical networks with the mobility and ubiquity of wireless networks. This article reviews the potential of integrating the wireless and optical access networks for future broadband access networks taking into account the energy consumption and energy modeling for evaluating the energy efficiency of such networks